Thirty Days has September : Cool Ways to Remember Stuff - Chris Stevens (Buster Books, 2008)
Thirty Days Has September helps with learning all of those confusing rules of language and mathematics, and those tricky facts from science, history and geography. It makes a lovely gift from parent to child and a perfect learning companion to help all school children. It is a treasure trove of easy methods to take important information from the back of the mind to the tip of children's tongues.